Effect of gas quantity on two-phase flow characteristics of a mixed-flow pump - Qiang Fu (Advances in Mechanical Engineering, 2016)
The inlet gas quantity has a great influence on the performance and inner flow characteristics of a mixed-flow pump. In this article, both numerical and experimental methods are used to carry out this research work. The effects under the steady gas volume fraction state and the transient gas quantity variation process on the mixed-flow pump are investigated and compared in detail. It could be concluded that the head of the mixed-flow pump shows slight decline at the low gas volume fraction state, while it decreases sharply at the high gas volume fraction state and then decreases with the increasing gas quantity. There is an obvious asymmetric blade vapor density on the blade suction side under each cavitation state. The cavities can be weakened obviously by increasing the inlet gas volume fraction within a certain range. It has little influence on the internal unsteady flow of the mixed-flow pump when the gas volume fraction is less than 10%, but the pump starts to operate with a great unsteady characteristic when the inlet gas volume fraction increases to 15%.